PENGARUH LABA AKUNTANSI, ARUS KAS OPERASI, DAN NILAI BUKU EKUITAS TERHADAP HARGA SAHAM (STUDI PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Wa Ode Irma Sari; Ditya Wardana (RISTANSI: Riset Akuntansi, 2022)
This research aims to verify and analyze the correlation between Accounting Profit, Operating Cash Flow, and Book Value of Equity Against to Stock Prices. Causal associative is this type of research with a population of manufacturing companies on Food and Beverage Companie sub-sector listed on the IDX from 2017-2019. Pusposive sampling is a sampling technique used as many as 36 samples. Documentation technique is the data collection method used, multiple linear regression analysis is the analytical tool used. The results of this study exhibit that Accounting Profit and Operating Cash Flow have not show any influence on Stock Prices. Meanwhile, the book value of equity has an effect on stock prices.